3D kinematic mandible model to design mandibular advancement devices for the treatment of obstructive sleep apnea - García Reyes, Marcos; Cabrera Castillo, Juan A.; Bataller-Torras, Alex; Postigo-Pozo, Sergio; Castillo-Aguilar, Juan Jesús (Springer, 2020)
Mandibular advancement devices (MADs) are one of the treatments used for Obstructive sleep apnea (OSA). MADs try to maintain the mandible in an advanced position to keep the upper airways open when sleeping. To achieve this goal, most current MADs limit the mouth opening to a few millimetres. The study of the kinematic behaviour of the patient’s jaw is essential in order to design devices that allow greater aperture ranges. For this purpose, a 3D multibody model that reproduces jaw movement has been developed in this work. To this end, the movement of the lower incisor has been determined by means of a vision system and reflective markers. In addition, the kinematics of the temporomandibular joint has been modelled. Next, the device is designed and printed using a cam–follower mechanism. This way, the cam profiles and the followers are optimally designed and positioned for each patient depending on the physiognomy of the jaw and the opening and advancing movement prescribed by the specialist.
Keywords: Mandíbula; Maxilares; Mandibular advancement device; 3D mandible kinematics; Cam–follower mechanism; 3D printed devices